Simplified model for predictive direct power control with fixed switching frequency for grid-tie inverters - Ngo, Van Quang Binh; Nguyen, Khanh-Quang; Hoang, Dinh-Long; Nguyen, Tu-Ha (Hue University Journal of Science: Natural Science, 2024)
This study exhibits a simplified direct power control strategy based on the model predictive control for grid-tie inverters. To solve the problem of the variable switching frequency in the classical finite control set model predictive control (FCS-MPC), we combined the inverse predictive model and space vector modulation to calculate the desired inverter voltage. Furthermore, the computational burden is reduced thanks to the elimination of the optimization loop. A comparative study indicated that the proposed approach achieved better steady-state control performance concerning the low total harmonic distortion of the current model compared with the traditional FCS-MPC while guaranteeing a fast dynamic response. The effectiveness and feasibility of the proposed method were confirmed via simulations and experimental results.